UPAYA PENGELOLAAN BRANDING HOTEL MELALUI OPTIMALISASI MEDIA SOSIAL SEBAGAI KUNCI KESUKSESAN DI HOTEL PANTAI MERAK KOTA CILEGON - Khaeruman, Khaeruman; Komarudin, Mochamad Fahru; Mukhlis, Ahmad; Suflani, Suflani; Hidayat, Ardi; Afriani, Raden Irna (Yayasan Education and Social Center, 2023)
Hotel branding management is a strategic aspect in achieving the success of a hotel company, including Merak Beach Hotel in Cilegon City. Community service activities are focused on optimizing social media as the main key in improving the success of hotel branding management. The results of this activity show that media and public relations have an interdependent relationship, where the role of public relations is very important in building relationships with external media or media relations to create strong company branding. Media management is no longer limited to conventional platforms, but develops in the use of modern media, especially media based on internet technology. Merak Beach Hotel overcomes challenges in media relations by shifting focus to social media, especially Facebook. Nevertheless, the function of media relations is recognized as integral in branding strategies. The hope is that management can expand the function of media handling not only to internal media, but also externally. The important role of media and public relations in branding strategy is evident, it is expected that these steps improve branding management and strengthen relationships with related parties through social and external media